Functionalization of carbon nanotubes with bovine plasma biowaste by forming a protein corona enhances copper removal from water and ecotoxicity mitigation. Issue 8 (11th July 2022) - Martins, Carlos Henrique Zanini; Côa, Francine; Da Silva, Gabriela Helena; Bettini, Jefferson; De Farias, Marcelo Alexandre; Portugal, Rodrigo Villares; Umbuzeiro, Gisela de Aragão; Alves, Oswaldo Luiz; Martinez, Diego Stéfani Teodoro
Abstract : Functionalization of carbon nanotubes through protein corona formation with bovine plasma is a novel waste-to-wealth approach in agri-environmental nanoscience towards remediation of pollutants from water. Abstract : Water remediation is a current challenge in environmental science and technology. Functionalization is a pivotal step toward the application of carbon nanotubes for water remediation. Bovine plasma is an abundant agro-industrial biowaste that can be exploited as a low-cost source of biomolecules in green nanotechnologies. Here we show the functionalization of oxidized multiwalled carbon nanotubes with bovine plasma by forming a protein corona (BP@MWCNT) for copper removal from water linked to ecotoxicity mitigation for the first time. Cryogenic transmission electron microscopy (Cryo-TEM) showed that corona thickness is a function of nanotube diameter. The functionalization of nanotubes increased the dispersion stability ( ca. 90%) and the removal of copper ions from water ( ca. 400%) when compared to oxidized nanotubes. Importantly, BP@MWCNT did not show any acute toxicity (48 h) to Daphnia similis up to 100 mg L −1 and mitigated the copper toxicity ( ca. 100%) to this aquatic model organism in co-exposure assays. Our results demonstrate the significance of the environmental dimensions of biomolecular coronas in mediating the nanobiointeractions and ecotoxicity of carbon nanotubes. In addition, considering life cycle assessment, BP@MWCNT was easily removed from water with aluminum sulphate treatment. Surface functionalization of carbon nanotubes with bovine plasma (corona formation) is therefore a novel strategy for the removal of pollutants from water; connecting agricultural wastes and nanomaterial functionalization towards eco-friendly and waste-to-wealth approaches in agri-environmental nanotechnology.